2008
DOI: 10.1111/j.1365-2133.2008.08804.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of antimalarial treatment on IL-1β, IL-6 and TNF-α mRNA expression on UVB-irradiated skin in systemic lupus erythematosus

Abstract: These results demonstrate the local inhibitory effects of chloroquine on UVB-induced upregulation in the mRNA expression of proinflammatory cytokines in irradiated skin of SLE patients, and provide further insight into the apparent immunomodulatory, anti-inflammatory and photoprotective properties of chloroquine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 30 publications
1
39
1
2
Order By: Relevance
“…Two other pro-inflammatory cytokines, IL-6 and IL-10, were also reported to be involved in UVBinduced apoptosis. IL-6 expression is significantly lower in UVB-irradiated skin cells while large amounts of IL-10 are produced in the meantime [17,38]. In our study we found that inhibition of CRTAC1 gene expression could reduce the amounts of TNF-α and IL-6, but increase IL-10 in interference group.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Two other pro-inflammatory cytokines, IL-6 and IL-10, were also reported to be involved in UVBinduced apoptosis. IL-6 expression is significantly lower in UVB-irradiated skin cells while large amounts of IL-10 are produced in the meantime [17,38]. In our study we found that inhibition of CRTAC1 gene expression could reduce the amounts of TNF-α and IL-6, but increase IL-10 in interference group.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, TNF-α is an important mediator of immunity and inflammation, and it was reported to be involved in UVB-induced apoptosis of keratinocytes [16]. Wozniacka et al reported that three months of chloroquine treatment appeared to block UVB-induced up-regulation of IL-1β, IL-6 and TNF-α expression in non-diseased skin of systemic lupus erythematosus patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…4AQs inhibit replication of HIV, SARS coronavirus, and infl uenza [ 10 , 38 , 136 ] 26. Chloroquine blocked production of IL-1β, IL-6, and TNF-α caused by ultraviolet irradiation of skin of normal subjects but had no effect on expression of these cytokines in unirradiated skin [ 223 ] 27. Chloroquine stimulated nitric oxide production in the kidney and brain with increased vasopressin and natriuresis [ 224 ] 28.…”
Section: Negative Studies On Mechanism Of Action Of 4-aminoquinolinesmentioning
confidence: 91%
“…Of particular interest in relation to the skin reactions that occur in SLE are the observations of Wozniacka et al (2008) in which mRNA levels for IL-1 b , IL-6 and TNF a were measured in UV-radiated biopsied skin sites of 14 patients with SLE before and after monotherapy with CQ phosphate 125 mg b.i.d. for 3 months.…”
Section: Cytokine Production and Actionsmentioning
confidence: 99%